The Effect of Compressive Stress on Ultrasonic Pulse Velocity in Concrete for Compressive Strength Prediction - Ng, Chee Khoon; Chai, Peng How; Ting, Sim Nee; Kuan, Hoo Tien Nicholas (International Journal of Integrated Engineering, 2024)
Ultrasonic pulse velocity (UPV) has been a popular non-destructive testing method for prediction of concrete strength. This leads to development of two major types of concrete compressive strength prediction models using measured UPV values, namely the exponential function and the power function. A simpler exponential function, recognised as one of the earliest, has proven to be more accurate in predicting the concrete compressive strength. From this study, it was observed that measured UPV increases with the increase in stress-to-strength ratio of up to 0.25, and the measured UPV decreases thereafter. The increase in UPV will lead to overestimation of concrete compressive strength by up to 15%. However, if ? of compressive strength is considered as service stress, then the overestimation of concrete compressive strength will be lower at about 8%, and may even register a slight underestimation occasionally; due to the decrease in measured UPV values beyond stress-to-strength ratio of 0.25.